Analysis of “true extrauterine growth retardation” and related factors in very preterm infants—A multicenter prospective study in China - Shen, Wei; Wu, Fan; Mao, Jian; Liu, Ling; Chang, Yan-Mei; Zhang, Rong; Zheng, Zhi; Ye, Xiu-Zhen; Qiu, Yin-Ping; Ma, Li; Cheng, Rui; Wu, Hui; et al. (Frontiers in Pediatrics, 2022)
Objective: To investigate the incidence and related factors of extrauterine growth retardation (EUGR) and “true EUGR” in very preterm infants (VPI) from different regions of China. Methods: Clinical data of VPI were prospectively collected from 28 hospitals in 7 different regions of China from September 2019 to December 2020. The infants were divided into a small for gestational age (SGA) group or non-SGA group at birth, with non-SGA infants at 36 weeks of gestation or at discharge being further divided into a EUGR group or a non-EUGR group. Infants in the EUGR and non-SGA group were defined as “true EUGR”. The general information of VPI, such as maternal complications during pregnancy, use of enteral nutrition and parenteral nutrition, and complications during hospitalization were compared between the groups. Results: Among the 2,514 VPI included in this study, 47.3%, 41.5%, and 33.3% of VPI were below the 10th percentile, and 22.6%, 22.4%, and 16.0% of VPI were below the 3rd percentile for weight, height, and head circumference at 36 weeks of gestation or at discharge, respectively, by the percentile on the 2013 Fenton curve. The incidences of EUGR and “true EUGR” evaluated by weight were 47.3% and 44.5%, respectively. Univariate analysis showed that there were statistically significant differences in the aspects of perinatal and nutritional characteristics, treatment, and complications between the groups. Multivariate analysis showed that in non-SGA infants, the cumulative caloric intake during the first week was a protective factor for “true EUGR”, while days to reach total enteral nutrition, late initiation of human milk fortifier, and moderate to severe bronchopulmonary dysplasia were independent risk factors for “true EUGR”. Conclusion: More attention should be paid to the nutritional management of VPI to prevent “true EUGR”. Cumulative caloric intake should be ensured and increased during the first week, total enteral nutrition should be achieved as early as possible, human milk fortifier should be added early, and moderate to severe bronchopulmonary dysplasia should be prevented. These strategies are very important for reducing the incidence of “true EUGR” in VPI.